(untitled) (INNOVATIVE ECONOMY, 2025)
Ivashchuk I.O., Ivashchuk O.V., Nahirna N.I. TOOLS OF ECONOMIC DIPLOMACY IN ENSURING FOOD SECURITY Purpose. The aim of the article is to study the role of tools of economic diplomacy in ensuring food security, identification of effective measures that contribute to the stability of food systems and their reform in the context of global challenges. Methodology of research. A set of scientific methods was used to achieve the goal of the study, in particular: the abstract and logical method was used to formulate generalizations and conclusions based on the results of the analysis of the relationship between economic diplomacy and food security; methods of analysis and synthesis were used to substantiate theoretical approaches to economic diplomacy, to substantiate the impact of its tools on food security; comparative analysis – to study the experience of leading countries in the world in using tools of economic diplomacy to develop food systems and ensure the protection of agricultural producers; empirical analysis – to assess the policy of protectionism and the use of restrictive measures by countries in international trade, the impact of Ukraine’s economic diplomacy tools on its foreign trade and food security in the world; institutional analysis – to identify the role of institutions (including funds) in solving food issues; the method of visual analysis was used to visualize the results of the study through graphs, charts and tables. Findings. The multifaceted nature of the problem of food security is substantiated. The directions of its research in the scientific field are analysed. It is confirmed that research on food security through the prism of economic diplomacy is not frequent in the domestic scientific literature. However, in practice, countries use mechanisms of bilateral and multilateral cooperation to solve food security problems. It is substantiated that food security is significantly affected by changes in the geopolitical and geo-economics order, a crisis of confidence in international organizations, climate change and environmental policy. The main tools of economic diplomacy, with which it affects food security, are identified. The landscape of economic diplomacy is characterized by the intervention of countries in international trade that are protectionist in nature. The role of agrarian protectionism for food security is determined. The state of protection of agricultural producers in 2023 in individual countries of the world is analysed. The problem of foreign trade regulation for Ukraine and the main barriers, including in the agricultural sector, are revealed. The role of multilateral diplomacy in ensuring food security is revealed. The programs of individual countries and funds aimed at overcoming the food crisis and maintaining food security are analysed. The role of Ukraine in ensuring global food security and the main challenges it experiences in connection with the war are argued. The role of regional integration in food security is confirmed. Measures are proposed for the effective use of economic diplomacy tools to ensure food security. Originality. The scientific novelty of this study lies in the comprehensive analysis of economic diplomacy tools aimed at ensuring food security in the face of modern global challenges; substantiation of their role in stabilizing food systems in the context of climate change, geopolitical instability, social and economic inequality. Practical value. The practical value of the study lies in the fact that the approaches developed in it to the use of economic diplomacy tools to ensure food security and the conclusions drawn can be used by food security actors at all levels of its functioning, including in the process of improving state policy in the field of food security, integration into educational programs for training specialists in international relations and international economic relations. Key words: geopolitical uncertainty, food security, agriculture, economic diplomacy, tools of economic diplomacy, bilateral and multilateral cooperation, protectionist policy, agrarian protectionism, international trade, foreign trade of Ukraine, WTO, financing of food security programs.